(untitled) (Baghdad Science Journal, 2019)
The research is dealing with the absorption and fluorescence spectra for the hybrid of an Epoxy Resin doped with organic dye Rhodamine (R6G) of different concentrations (5*10-6, 5*10-5, 1*10-5, 1*10-4, 5*10-4) Mol/ℓ at room temperature. The Quantum efficiency Qfm, the rate of fluorescence emission Kfm (s-1), the non-radiative lifetime τfm (s), fluorescence lifetime τf and the Stokes shift were calculated. Also the energy gap (Eg) for each dye concentration was evaluated. The results showed that the maximum quantum efficiency 62 % and maximum stokes shift 96 nm was obtained in dye concentration 5*10-6 and 1*10-4. The energy gap ranges between 1.066 eV to 1.128 eV depending proportionally on the dye concentrations.